Comparison of thermal neutron and hard X-ray dark-field tomography - Gustschin, Alex; Neuwirth, Tobias; Backs, Alexander; Viermetz, Manuel; Gustschin, Nikolai; Schulz, Michael; Pfeiffer, Franz (Journal of Imaging, 2021)
High visibility (0.56) neutron-based multi-modal imaging with a Talbot–Lau interferometer at a wavelength of 1.6 Å is reported. A tomography scan of a strongly absorbing quartz geode sample was performed with both the neutron and an X-ray grating interferometer (70 kVp) for a quantitative comparison. Small scattering structures embedded in the absorbing silica matrix were well resolved in neutron dark-field CT slices with a spatial resolution of about 300 µm. Beneficial effects, such as monochromaticity and stronger penetration power of the used neutron radiation, helped to avoid the beam hardening-related artificial dark-field signal which was present in the X-ray data. Both dark-field modalities show mostly the same structures; however, some scattering features appear only in the neutron domain. Potential applications of combined X-ray and neutron multi-modal CT enabling one to probe both the nuclear and the electron density-related structural properties are discussed. strongly absorbing samples are now accessible for the dark-field modality by the use of thermal neutrons.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Hard X-ray dark-field imaging; Neutron dark-field imaging; Neutron grating interferometry; Neutron imaging; X-ray grating interferometry